Selective Emotional Dysregulation in Splenium Agenesis. A Case Report of a Patient With Normal Cognitive Profile - Palermo, Sara; Andò, Agata; Salatino, Adriana; Sirgiovanni, Stefano; De Faveri, Luana; Carassa, Antonella; Valentini, Maria C.; Morese, Rosalba (Frontiers in Psychology, 2019)
Objectives: Patients with lesions of the corpus callosum are rare and may present different symptoms of the disconnection syndrome. However, to-date studies on callosotomized patients have not been conclusive, likely because of the non-uniform nature of clinical features, the extent of resection, and methods used to investigate specific and related deficits. Agenesis of the corpus callosum may be asymptomatic and discovered incidentally or associated with very slight deficits diagnosed during neurological examinations. In this study, we reported a case of an apparently completely asymptomatic 23-year-old woman with appreciable agenesis of the splenium of the corpus callosum. Methods: She underwent a neurological evaluation, a comprehensive battery of neuropsychological tests to identify any subclinical dysfunction that may affect the functionality of the subject in the daily life. Specifically, the possible presence of emotion dysregulation was examined by using a self-report questionnaire. Results: She showed normal neuropsychological and emotional functioning, performing efficiently on tests measuring acquired brain impairment. Discussions: The present case is discussed in terms of neuroplasticity – with a focus on putative compensatory mechanisms – emphasizing the variegated clinical feature patterns of brain defects present from birth.